2018
DOI: 10.1080/07420528.2018.1456447
|View full text |Cite
|
Sign up to set email alerts
|

Association of the melatonin circadian rhythms with clock 3111T/C gene polymorphism in Caucasian and Asian menopausal women with insomnia

Abstract: A comparative analysis of melatonin circadian rhythms in Caucasian (incoming population) and Asian (indigenous population) menopausal women with/without sleep disorders depending on the genotype of Clock 3111T/C gene polymorphism was realized.The melatonin level in the saliva was determined four times a day (6:00-7:00, 12:00-13:00, 18:00-19:00, 23:00-00:00 h). The Caucasian women-carriers of the TT-genotype with insomnia as compared to control group-had a higher morning melatonin level and a lower night melato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 66 publications
1
14
0
2
Order By: Relevance
“…In postmenopause, the morning melatonin peak has been also noted, regardless of the presence of insomnia [57]. The present study further have revealed the association of melatonin secretion circadian rhythms with Clock 3111T/C gene polymorphism in Caucasian patients with insomnia, consisting of an increased hormone level in early morning hours in carriers of the TT-genotype, which allows considering 3111T allele as risky in the formation of melatonin circadian rhythm disturbances in these patients [58]. Moreover, differences in the circadian rhythms of melatonin in the Asian women depending on the genotype of the Clock 3111T/C polymorphism have not been found.…”
Section: Discussionsupporting
confidence: 71%
“…In postmenopause, the morning melatonin peak has been also noted, regardless of the presence of insomnia [57]. The present study further have revealed the association of melatonin secretion circadian rhythms with Clock 3111T/C gene polymorphism in Caucasian patients with insomnia, consisting of an increased hormone level in early morning hours in carriers of the TT-genotype, which allows considering 3111T allele as risky in the formation of melatonin circadian rhythm disturbances in these patients [58]. Moreover, differences in the circadian rhythms of melatonin in the Asian women depending on the genotype of the Clock 3111T/C polymorphism have not been found.…”
Section: Discussionsupporting
confidence: 71%
“…The study included 403 menopausal women from both Caucasian and Asian races, who were evaluated based on their diurnal sleepiness (using subthreshold insomnia and Epworth Sleepiness Scale), polymorphic genotyping, and a four-time per day collection of saliva samples for melatonin determination. Higher melatonin levels (1.40 times, p < 0.05) were detected in the early morning hours in the carriers of the TT-genotype compared to that in a group of carriers of the minor 3111C-allele [89]. Significant differences in the melatonin levels were found between the control and main group of Asian women carriers of the TT-genotype.…”
Section: Clockmentioning
confidence: 73%
“…Significant differences in the melatonin levels were found between the control and main group of Asian women carriers of the TT-genotype. This group had a lower hormone level during the day, evening, and night hours in women with insomnia (1.68, 1.80, and 2.13 times, respectively) [89]. It was postulated that in the course of evolution, the allele played a protective role in the development of insomnia [90].…”
Section: Clockmentioning
confidence: 93%
See 1 more Smart Citation
“…The present study further revealed the association of melatonin secretion circadian rhythms with Clock 3111T/C gene polymorphism in Caucasian patients with insomnia, consisting of an increased hormone level in early morning hours in carriers of the TT-genotype, which allows considering 3111T allele as risky in the formation of melatonin circadian rhythm disturbances in these patients. Moreover, differences in the circadian rhythms of melatonin in the Asian women with insomnia, depending on the genotype of the Clock 3111T/C polymorphism, were not found [39].…”
Section: Melatonin Is the One Of The Key Elements Of The Sleep-wake Cmentioning
confidence: 83%